Proceso atención de enfermería en paciente adulto con herida traumática séptico en pie izquierdo. - Salinas Moncayo, Jorge Abrahan (2022)
The attention of the nursing staff is of vital importance to achieve the prompt and effective recovery of the patient in conjunction with the treating physician, since it allows in the care practice to provide care to the patient in an adequate and systematic way. In the present clinical case, the Nursing Care Process used in a 27-year-old young adult patient with a septic traumatic wound in the left foot, who is admitted to the Baba Basic Hospital, is analyzed and is attended by the medical and nursing staff, the traumatic wound presented by the patient occurred as a result of a burn which was complicated by the infection presented due to poor hygienic habits causing his admission to the hospital unit and the need to apply medical and nursing procedures during his stay in the hospital , being able to show that during his stay in the hospital unit he evolved favorably. Nursing care activities must be contextualized in some theoretical model of professional praxis, and in the clinical case presented, Virginia Henderson's conceptual model was used based on basic needs and human development, which allows us to recognize the signs and patient's symptoms related to the infection presented and establish a nursing diagnosis. It is a support model to explain the alterations in functional patterns and nursing care techniques established by the NANDA, NOC, NIC taxonomy in patients with septic traumatic wounds in the left foot.